Counseling on life style modification and knowledge and belief of hypertension and its management among hypertensive patients visiting community based screening and management program in Eastern Nepal - Koirala, Bhawesh; Rauniar, Gajendra Prasad; Ghimire, Anup; Sharma, Sanjib Kumar (Journal of Chitwan Medical College, 2018)
Background: Hypertension is a global health problem with almost quarter of adults estimated to have high blood pressure. There are evidences showing effectiveness of lifestyle modification on the prevention and management of hypertension. The adherence to lifestyle modifications and medication depends upon knowledge and belief on management of hypertension and the counseling they received from medical staffs. Methods: In this prospective crossover study, 140 hypertensive patients were enrolled after getting written informed consent. This study was performed after obtaining the ethical clearance from Institutional Research Committee (IRC), BPKIHS, and Dharan. Data was collected using validated structured self-constructed questionnaire from the hypertensive patients visiting community program (KHDC) held on first Saturday of every month for follow-up. KHDC is a community based program for early detection and management of Kidney disease, Hypertension, Diabetes and Cardiovascular diseases. For descriptive statistics, percentage, mean, Standard deviation was calculated along with graphical and tabular presentation. Results: Out of 140 patients enrolled 52.1% were male. Majority of the patient were aged between 40-59 years of age (50.7%). Most of them were Aryans 55.7 % followed by Mongolians 44.3%. Mean of Systolic Blood pressure was 131.48(SD ± 16.57) and Mean of Diastolic Blood pressure was 81.7(SD ±9.57). Majority of patient believed that they have received appropriate counseling from the medical staffs in regards to appropriate diet, Body weight, Smoking cessation, Physical activity and risk and complication of hypertension. Overall knowledge rate was high on all items but 27.9% patients believed that treating with drugs is sufficient for the management of hypertension. Only 7.1 % of them were smokers whereas 24.3% consumed alcohol, 72.1 % patients were non vegetarians and most of them preferred average amount of salt in their meal 52.1%. However 44.3 % patients preferred low amount of salt. Sixty percentages of patients reported that they were doing physical exercise regularly. Conclusion: The knowledge and belief on the management of hypertension is high in the hypertensive patients visiting community based program for early detection and management of Kidney disease, Hypertension, Diabetes and Cardiovascular diseases. Further, most patients received the counseling on lifestyle modification which was reflected in their general behaviour.